Urinary proteomic analysis during pregnancy and its potential application in early prediction of gestational diabetes mellitus and spontaneous abortion - Wang, Xiangqing; Zhao, Mindi; Guo, Zhengguang; Song, Shuoning; Liu, Shixuan; Yuan, Tao; Fu, Yong; Dong, Yingyue; Sun, Haidan; Liu, Xiaoyan; Zhou, Dongdong; Zhao, Weigang; et al. (Annals of Translational Medicine, 2022)
The maternal physiological changes which occur during gestation are complex and affect diverse systems in the body. Elucidating the various changes that occur during pregnancy may assist with understanding maternal health and the factors affecting pregnancy outcomes.BackgroundThe maternal physiological changes which occur during gestation are complex and affect diverse systems in the body. Elucidating the various changes that occur during pregnancy may assist with understanding maternal health and the factors affecting pregnancy outcomes.A longitudinal cohort of 84 pregnant women was established. The urinary proteomes of women in different trimesters of pregnancy (6-8, 22-24, and 32-34 weeks) were characterized using data-independent acquisition tandem mass spectrometry. Gestational diabetes mellitus (GDM) was diagnosed at 24 to 28 weeks. Functional analysis of serial changed proteins was performed.MethodsA longitudinal cohort of 84 pregnant women was established. The urinary proteomes of women in different trimesters of pregnancy (6-8, 22-24, and 32-34 weeks) were characterized using data-independent acquisition tandem mass spectrometry. Gestational diabetes mellitus (GDM) was diagnosed at 24 to 28 weeks. Functional analysis of serial changed proteins was performed.Fifteen women had GDM, 50 were healthy, and 19 experienced spontaneous abortion (SA). Functional analysis showed that the urinary proteome reflected physiological and pathological changes during pregnancy. Compared to those of women with a normal pregnancy, the urinary proteomes of women with GDM and SA showed significant disease-related changes in insulin secretion and estrogen receptor activity, respectively, during the first trimester. Urinary protein during the first trimester of pregnancy achieved an area under the curve of 0.91 and 0.81 for GDM and SA, respectively.ResultsFifteen women had GDM, 50 were healthy, and 19 experienced spontaneous abortion (SA). Functional analysis showed that the urinary proteome reflected physiological and pathological changes during pregnancy. Compared to those of women with a normal pregnancy, the urinary proteomes of women with GDM and SA showed significant disease-related changes in insulin secretion and estrogen receptor activity, respectively, during the first trimester. Urinary protein during the first trimester of pregnancy achieved an area under the curve of 0.91 and 0.81 for GDM and SA, respectively.The urinary proteome has the potential to reflect serial changes of pregnancy progression; therefore, its use might facilitate early diagnosis of pregnancy complications.ConclusionsThe urinary proteome has the potential to reflect serial changes of pregnancy progression; therefore, its use might facilitate early diagnosis of pregnancy complications.